THE EFFECT OF DISCIPLINE AND TRAINING ON PERFORMANCE OF EMPLOYEES AT THE FIRE AND RESCUE SERVICE IN CITY ADMINISTRATION OF CENTRAL JAKARTA - Jon Muardi; Kwarnanto Rohmawan; Nurminingsih (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
The Fire and Rescue Service is a government apparatus with the duties, principal and functions in the field of prevention, fire prevention and rescue. Therefore, the performance of firefighters in their duty to combat fires needs to be analyzed. Because firefighters first take care of their personal safety as well as the safety of those around who need help. The purpose of this study is to analyze the effect of discipline and training on employee performance in the Central Jakarta City Fire Service Administration Department, written in Minister of Public Works Regulation No. 20 / PRT / M / 2009 CHAPTER II Section 5, concerning human resources and training education is held at the Center for Fire Fighting and Rescue Education and Training which aims to provide basic knowledge about prevention, management and rescue in the field of fire and other disasters. In improving the performance of work officers, training needs to be provided as needed, training that can regulate employees regularly so that there are no violations at work. This research method uses research instruments namely simple regression and multiple regression to find the correlation coefficient between discipline and training on employee performance. The finding reveals that work discipline has a direct and significant positive effect on employee performance. Likewise, work discipline has a direct and significant positive effect on training. Furthermore, training has a direct and significant positive effect on employee performance. Meanwhile, Discipline and Training have a positive and significant indirect effect on employee performance.